Phacoemulsification versus manual small incision cataract surgery in hard nuclear cataracts - Hesham A Enany (Delta Journal of Ophthalmology, 2018)
Purpose The aim of this study was to compare the clinical outcomes of phacoemulsification with that of manual small incision cataract surgery (MSICS) in cases of hard nuclear cataract. Patients and methods Eighty eyes of 80 patients with gradual painless diminution of vision, diagnosed as senile nuclear cataract grade 4 or higher according to Lens Opacities Classification System III (brown cataract), were studied. These eyes were divided randomly into two groups: group A included 40 eyes treated by phacoemulsification by the vertical chopping technique and group B included 40 eyes treated by MSICS by the viscoexpression technique. Results One day postoperatively, the corrected distance visual acuity was at least 6/18 in 21 (52.5%) patients in the MSICS group and in nine (22.5%) patients in the phacoemulsification group. The difference was statistically significant (P=0.01). A postoperative increase in intraocular pressure was recorded in one (2.5%) case in the phacoemulsification group. On the first postoperative day, 11 (27.5%) cases in the MSICS group and 13 (32.5%) cases in the phacoemulsification group developed postoperative iritis, with no statistically significant difference between both the groups. Conclusion Both phacoemulsification and MSICS achieved comparable and excellent visual outcomes for treatment of hard brown cataract, with lower complications rates and earlier postoperative visual rehabilitation in small incision cataract surgery.